2022
DOI: 10.1111/febs.16418
|View full text |Cite
|
Sign up to set email alerts
|

Caspases help to spread the message via extracellular vesicles

Abstract: Cell‐cell communication is an essential aspect of multicellular life, key for coordinating cell proliferation, growth, and death in response to environmental changes. Whilst caspases are well‐known for facilitating apoptotic and pyroptotic cell death, several recent investigations are uncovering new roles for these enzymes in biological scenarios requiring long‐range intercellular signalling mediated by extracellular vesicles (EVs). EVs are small membrane‐bound nanoparticles released from cells that may carry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 201 publications
0
9
0
Order By: Relevance
“…Annexin/PI staining was used to assess the percentage of cumulative apoptotic cells which was 99.45% (53.37% early & 46.08% late apoptotic cells) and 99.60% (52.50% early & 47.10% late apoptotic cells) at a 12h time point in BM-MSCs & WJ-MSCs respectively, whereas at 24h there was a decline in the number of apoptotic cells in both the groups (99.30% and 89.28% respectively) (Figure 1B, C). Furthermore, at this time point, the cells displayed the hallmark features of apoptosis induction including significant morphological alteration, cell blebbing, and shrinkage [26] (Figure 1A). Induction of apoptosis was also validated via western blotting in both the tissue-specific MSCs in terms of the Caspase 3 expression (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexin/PI staining was used to assess the percentage of cumulative apoptotic cells which was 99.45% (53.37% early & 46.08% late apoptotic cells) and 99.60% (52.50% early & 47.10% late apoptotic cells) at a 12h time point in BM-MSCs & WJ-MSCs respectively, whereas at 24h there was a decline in the number of apoptotic cells in both the groups (99.30% and 89.28% respectively) (Figure 1B, C). Furthermore, at this time point, the cells displayed the hallmark features of apoptosis induction including significant morphological alteration, cell blebbing, and shrinkage [26] (Figure 1A). Induction of apoptosis was also validated via western blotting in both the tissue-specific MSCs in terms of the Caspase 3 expression (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-3 has been found to cleave Rho-associated protein kinase (ROCK I), which leads to the remodelling of actin and microtubules present at the plasma membrane, therefore resulting in membrane blebbing and EV formation. However, the precise mechanism for the heightened secretion remains unclear [26,30].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously discovered that nonapoptotic caspase action mediates the increased release of large MkEVs under very low levels of shear stress 13 . Such caspase activity is commonly implicated in the biogenesis of other EVs, 64 and may provide a fruitful starting point for future investigations into MkEV cargo loading specifically. Figure 11 illustrates common mechanisms by which biomechanical force mediates EV biology, providing additional avenues of inquiry for future MkEV research 25…”
Section: Discussionmentioning
confidence: 99%
“…Related to this, failed apoptosis and nonapoptotic functions of the apoptosis machinery have implications for tumor emergence and progression (reviewed in 288–290 ). Non‐canonical functions of caspases, for example, may be important in driving proliferation 291 and EV biogenesis and activities 292 . In Drosophila , it was found that translocation of the initiator caspase, Dronc to the plasma membrane by the unconventional myosin, Myo1D can activate AiP‐like proliferation, independently of apoptosis through activation of the fly NADPH oxidase, Duox which generates reactive oxygen species 293 .…”
Section: Programming Of the Tumor Microenvironment By Apoptosismentioning
confidence: 99%